Assessing the Impact of Nonlinear Pedagogy on Student Engagement in Physical Education - Aliya Ahmetkarimovna Kuralbayeva; Asel Tasova; Malik Sultanbek; Mariya Jazdykbayeva; Saule Kozhageldieva; Zhanar Shalabaeva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: this study explores the effectiveness of nonlinear pedagogy in physical education compared to traditional teaching methods. nontraditional approaches like nonlinear pedagogy have gained attention for their potential to enhance learning through increased engagement and interaction.